Otolith atlas of fish of the Sinos River - Bremm,CQ. (2014)
Otoliths are calcium carbonate structures located in the inner ear of fish; they are responsible for hearing and balance. The inner ear has three pairs of otoliths: the lapilli, the sagittae and the asterisci. The sagittae otoliths are the largest and their format is species-specific. Because of their composition, otoliths can resist to the digestive tract of ichthyophagous species, and they can be used as an important tool for identifying species of fish found in stomach contents. The purpose of this work is to provide a photographic guide of the sagittae otoliths of the main fish species from the Sinos River. This atlas consists of photographs of the sagittae otoliths of 36 species belonging to 15 families distributed in five orders.